Rancangan Pembelajaran Individual Pada Mata Pelajaran IPA Secara Daring Menggunakan Aplikasi Google Classroom Di Sekolah Dasar - Anisya; Madella Devitri (Universitas Negeri Padang, 2023)
In the days of recruits many students perform individual studies at home to reduce the impact of covid-19 and one of them affects elementary school children who require them to study individually in their own homes with parents accompanying them to understand the learning given by teachers Work in their homes and then put together the following week, teachers who are doing the learning process through the whatsapp application accompanied by student parents during an online class, and some schools have been using e-learning as learning stations during sessions. Much of the complaints experienced during online study are particularly with science subjects which in this science class there is some material that students should do: the practice of applying the material that is being studied with the pandemic covid-19 makes ita little difficult for students or elementary school students to understand what would be done Growth and development such as the example of green beans to toge and so on. An individual learning design in a classroom where students transition from learning to teaching together in a single room to a room where this individual design is focused more effectively on the individual, giving more downloadable materials and video links that are watched for materials that require performing practices such as growth and development materials in green beans Into toge and other practice materials The challenge of applying such vast scientific pupil individualized study, the vast storage of mobile phones to keep Google classroom and video practice and so on.